Effectiveness of commercial biological and chemical extracts for the control of nematodes in coffee tree in Chiapas - Cepeda Siller, Melchor; Ochoa Fuentes, Yisa María; Cerna Chávez, Ernesto; Garrido Cruz, Fabiola; González Ruíz, Aideé; Hernández-Juárez, Agustín (Revista Mexicana de Ciencias Agrícolas, 2020)
Phytoparasitic nematodes constitute one of the main pathogens that affect the cultivation of the coffee tree Coffea arabica L., causing reductions in yield between 15 and 60%. The objective of this research was to evaluate the effectiveness of the biological extracts of the nematicide Nemaxxion XT Plus, for the control of the nematodes Meloidogyne incognita and Pratylenchus sp., associated with the cultivation of coffee. Five treatments with five replications were considered under a randomized complete block design: Nemaxxion XT Plus (2 L ha-1, 4 L ha-1, 6 L ha-1), Nemacur® 400 CE and control. Nematode populations were counted in 100 g of soil before applying the treatments and 120 days after the experiment was installed. For counting, the nematodes were extracted by the Baerman funnel method. For M. incognita, the number of second instar juveniles, adult males and females, was counted and for Pratylenchus sp., the filiform adult males and females were counted. The evaluation demonstrated the effectiveness of the treatments for the control of nematode populations, these treatments presented a considerable reduction of the populations, with an average survival of 1.2-3.4 nematodes of M. incognita and 2.2-4.4 nematodes of Pratylenchus sp., of these, Nemaxxion XT Plus at 6 L ha-1 presented the greatest population reduction and efficiency over the two populations, with 99.08 and 92.87% respectively, presenting itself as an alternative for a more sustainable agriculture.